Global trends in thermal burn burden, 1990–2021: a comprehensive analysis for the global burden of disease study 2021 - Zhang, Yuke; Chen, Qingsong; Wang, Ru; Guo, Linfen; Li, Peiyu; Deng, Ke; Xiao, Haitao; Xu, Xuewen (Frontiers in Public Health, 2025)
BackgroundThe purpose of this study is to explore the global burden of thermal burns from 1990 to 2021 and to predict the trends in thermal burn burden up to 2040.MethodsWe utilized data from the Global Burden of Disease Study 2021 to assess the incidence, prevalence, and years lived with disability (YLDs) of thermal burns at the global, regional, and national levels. Decomposition analysis was performed to quantify the relative contributions of epidemiological changes, age structure shifts, and population growth to the thermal burn burden. Frontier analysis was employed to evaluate the potential improvements in the thermal burn burden that could be achieved given a country’s development status. A Bayesian age-period-cohort model was used to predict burden trends up to 2040.ResultsIn 2021, the global numbers of thermal burn incident cases and YLDs were approximately 6.19 million and 2.67 million, respectively, representing decreases of 9.44 and 11.86% from 1990. The prevalent cases were around 104.76 million, an increase of 11.38% from 1990. The age-standardized rates of incidence, prevalence, and YLDs all showed declines. Decomposition analysis indicated that population growth is the primary factor hindering the reduction of the thermal burn burden. Frontier analysis suggested that countries at various development levels have the potential to improve the thermal burn burden. By 2040, the number of thermal burn incident cases is predicted to decline, while the numbers of prevalent cases and YLDs will increase.ConclusionThe global burden of thermal burns has been partially alleviated, but it will continue to persist. For low socio-demographic index countries, it is necessary to adopt targeted healthcare measures tailored to their specific circumstances alongside social development to achieve optimal management of thermal burns.